D. D. jak dreszcz demencji - Serkowska, Hanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The claim here is that cultural representations of dementia may benefit from the structure of crime fiction which appears therefore to be among the theme most suited genres. We do not know enough about the disease or its etiology (the “culprit” remains unknown), hence the situation of the sufferer befits that of enigma or suspense, fear or confusion, doubt and presumption, standardly deployed by detective stories. Crime fiction narratives underscore that which is at stake in dementia: the riddle of disappearing of the person affected, the puzzle of memory loss, the identity doubt which extends to the relative when he or she is not recognized by the sufferer. By turning to a detective genre, Alzheimer’s novel profits from the genre’s growing popularity, owing to the reading public’s demand for challenges enhancing “mind reading” competences and training predictive abilities. The latter are more in demand as neurocognitive standards of readers grow.